Давньоруські поселення поблизу с. Бучак - Петрашенко, В.О.; Козюба, В.К. (Археологія, 2005)
У статті опубліковано давньоруські матеріали з розкопок багатошарового поселення поблизу с. Бучак Канівського р-ну Черкаської обл. Досліджено ландшафтно-топографічну структуру території, реконструйовано напрямки господарської діяльності населення та адміністративний устрій регіону. Статья посвящена пространственно-топографическому анализу группы древнерусских поселений, расположенных в окрестностях с. Бучак Каневского р-на Черкасской обл. Опубликованы материалы многослойного поселения в ур. Рожана Крыныця, в научный обиход введена большая коллекция вещей, полученных со смыва побережья Каневского водохранилища. Исследована ландшафтно-топографическая структура территории компактно расположенной группы памятников (2 городища, 4 поселения, могильник), отмечено ведущее место поймы в территориальной структуре региона. На основании анализа вещевого комплекса, планиграфии центрального раскопа и возможностей ресурсной зоны сделан вывод о приоритетном развитии животноводства и ремесел в хозяйственной структуре поселка. Весь комплекс исследованных археологических артефактов позволяет говорить о принадлежности поселения у с. Бучак местной знати. The article analyzes spatial topography of a group of Ancient Rus’ settlements located in the vicinity of Buchak village in the Kaniv Region of Cherkassy Oblast’. The materials on a multi-layer settlement located at the Rozhana Krynytsya tract are published. A large collection of artifacts obtained from the washing-away of the bank of the Kaniv water storage basin is introduced to the scientific world. Landscape and topographic structure of the territory of a tightly situated group of monuments (2 hill-forts, 4 settlements, and a burial ground) is studied, the primary role of flood-lands within the territorial structure of the region is noted. The analysis of material assemblage, planigraphy of the central excavation trench and the possibilities of the resource zone lead to a conclusion regarding the priority development of animal husbandry and crafts within the economic structure of the settlement. The whole assemblage of the archaeological artifacts under study permits us to conclude that the settlement near the village of Buchak belonged to the local aristocracy.